HUMAN VULNERABILITY IN THE CONTEXT OF CONTEMPORARY WAR AND THE CRISIS OF NORMATIVE ORDER - Shorina, Tetiana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Introduction. The article examines human vulnerability in the context of contemporary war and the crisis of normative order from a socio-philosophical perspective. Particular attention is given to how war not only produces new threats but also intensifies pre-existing forms of socially conditioned insecurity. The aim and tasks. The aim of the study is to clarify the socio-philosophical meaning of human vulnerability under contemporary wartime conditions. The tasks are to analyse vulnerability as an anthropological condition of human existence, to reveal its connection with socially produced insecurity and precarity, and to determine its significance for understanding the crisis of normative order. Research methods. The study employs socio-philosophical, critical-hermeneutic, and normative-analytical approaches. These methods make it possible to interpret vulnerability through the categories of dependence, freedom, recognition, insecurity, institutional protection, and to relate the lived experience of vulnerability to the limits of legal and political normativity. Research results. It is shown that vulnerability should be understood both as a universal condition of embodied and dependent human existence and as unevenly distributed across social contexts. The analysis distinguishes between precarity as an unevenly distributed condition of insecurity and precarization as the socio-historical process through which such insecurity is produced and normalized. War is interpreted as a factor that radicalizes already existing insecurity and exposes the gap between the formal language of rights and the actual selectivity of protection. Discussion. The analysis demonstrates that vulnerability cannot be reduced either to abstract human fragility or to the immediate consequences of military violence alone. Its heuristic value lies in connecting anthropological dependence, social precarity, and the asymmetrical functioning of contemporary normative institutions. Conclusions. The article concludes that human vulnerability in wartime reveals the contradiction between universalist claims of protection and their unequal implementation. In this sense, vulnerability becomes an important analytical category for understanding the crisis of normative order and the conditions of protecting human life in present-day society.